Efeito do porta-enxerto e da época de poda na duração das fases fenológicas e no acúmulo de graus-dia pela videira 'Niagara Rosada' - Tecchio, Marco Antonio [UNESP]; Moura, Mara Fernandes; Paioli-pires, Erasmo José; Terra, Maurilo Monteiro [UNESP] (Sociedade Brasileira de Fruticultura, 2013)
It was evaluated the influence of rootstocks 'IAC 766', 'IAC 572', 'IAC 313', 'IAC 571-6' and 'Ripária do Traviú' and the pruning periods in the duration of phenological stages and in the accumulation of degree-days on grape 'Niagara Rosada' .The experiment was conducted in Louveira, SP. The treatments consisted of five rootstocks and three times of pruning, the experimental design being used in a completely randomized split plot with five replications, and plots represented by rootstocks and the subplots were pruning. After pruning the grapevine, were realized evaluations for phenological stages, using the criterion of Eichhon e Lorenz (1984). ). In three seasons of pruning, based on phenological stages, it was calculated the length of the periods: pruning to budding, pruning to the beginning of the flowering, pruning to the beginning of fruiting, pruning to beginning of ripening of the bunches, pruning the beginning of the harvest. Taking as a basis the cycle length of the vine and the average daytime temperatures, it was calculated the accumulation of degree-days. Data were submitted to ANOVA and Tukey test at 5% significance level. It was obtained in the summer pruning the reduction in duration of the phenological stages of 'Niagara Rosada' grafted on the rootstock 'Ripária Traviú'. The longer duration of the cycle and accumulation of degree-day of 'Niagara Rosada' cultivar were obtained with the rootstocks 'IAC 572' and 'IAC 313' pruning in the winter.

Avaliaram-se a influência dos porta-enxertos 'IAC 766', 'IAC 572', 'IAC 313', 'IAC 571-6' e 'Ripária do Traviú' e da época de poda na duração dos estádios fenológicos e no acúmulo de graus-dia pela videira 'Niagara Rosada'. O experimento foi realizado em Louveira-SP. Os tratamentos consistiram na combinação de cinco porta-enxertos e três épocas de poda, sendo utilizado o delineamento experimental em blocos inteiramente casualizados, com parcelas subdivididas e cinco repetições, sendo as parcelas representadas pelos porta-enxertos,e as subparcelas, pelas épocas de poda. Após a poda da videira, foram realizadas avaliações dos estádios fenológicos, utilizando-se do critério de Eichhon e Lorenz (1984). Nas três épocas de poda, baseado nos estádios fenológicos, calculou-se a duração dos períodos: poda ao início da brotação; poda ao pleno florescimento; poda ao início da frutificação; poda ao início da maturação dos cachos, e poda à colheita. Tomando-se por base a duração do ciclo da videira e as temperaturas médias diárias, calculou-se o acúmulo de graus-dia. Os dados foram submetidos à análise de variância e teste Tukey, a 5% de significância. Obteve-se, na poda de verão, redução na duração dos estádios fenológicos da videira 'Niagara Rosada' enxertada sobre o porta-enxerto 'Ripária do Traviú. A maior duração do ciclo e do acúmulo de graus-dia da cultivar Niagara Rosada foi obtida com os porta-enxertos 'IAC 572' e 'IAC 313' nas podas de inverno.
Effect of rootstock and the pruning periods in the duration of phenological stages and in the accumulation of degree-days on grape 'Niagara Rosada'
Keywords: Vitis; clima; fenologia; porta-enxerto; Vitis; climate; phenology; rootstocks